INCIDENCE PATTERN OF SUCKING INSECT PESTS WITHIN PLANT CANOPY OF SELECTED COTTON (Gossypium Spp.) BT AND NON-BT CULTIVARS - N.V.V.S.D. PRASAD, Y. RAJASEKHAR , P.V. KRISHNAYYA and (The Journal of Research, PJTSAU, 2017)
In India, cotton (Gossypium Spp.) crop is damaged by several insect pests comprising of bollworms and sap sucking pests. The sucking pests include aphids, Aphis gossypii (Glover); leafhoppers, Amrasca biguttula biguttula (Ishida); whiteflies, Bemisia tabaci Genn.; and thrips, Thrips tabaci Lindeman that damage the crop with regular occurrence at different growth stages and reduce the growth and yield up to 21.20 per cent (Dhawan et al., 1988). Considering the importance of the sucking insect pests, the investigations were carried out on their incidence pattern within plant canopy.